Fixed-bed column adsorption of arsenic(V) by porous composite of magnetite/hematite/carbon with eucalyptus wood microstructure - Li, Yanhong; Zhu, Yinian; Zhu, Zongqiang; Zhang, Xuehong; Wang, Dunqiu; Xie, Liwei (Journal of Environmental Engineering and Landscape Management, 2018)
The fixed-bed column adsorption-desorption of As(V) by the porous composite of iron oxides and carbon with eucalyptus wood hierarchical microstructure (PC-Fe/C) was experimentally studied. The increase in the influent As(V) concentration and the inflow rate resulted in an earlier exhaustion of the column. The breakthrough curves indicated that a larger adsorbent mass, a smaller adsorbent grain size and a lower influent pH prolonged the column life span. The operating temperature had negligible effect. All breakthrough curves could be well fitted with the Thomas and Yoon–Nelson models. Under the condition of the influent flow rate of 5.136 mL/min, the influent As(V) concentration of 20 mg/L, the influent pH of 3, the adsorbent mass of 2 g, the adsorbent grain size of <100 mesh, and the operating temperature of 35 °C, the equilibrium adsorption capacity reached 10.49 mg/g, which was greater than those of natural/synthetic iron oxides adsorbents and iron-oxide-coated adsorbents.